2018
DOI: 10.1007/s00403-018-1804-1
|View full text |Cite
|
Sign up to set email alerts
|

Skin depigmenting action of silkworm (Bombyx mori L.) droppings in zebrafish

Abstract: The excrement of silkworms (Bombyx mori L.), referred to here as silkworm droppings (SDs), is used as a traditional drug in eastern medicine to treat skin diseases such as urticaria and atopy. However, the depigmentation effects of SDs have not previously been evaluated. We focused on the depigmentation effect of a methanol extract of SDs and isolated components of the extract using a zebrafish model system. (+)-Dehydrovomifoliol (M-1), (6R,7E,9R)-9-hydroxy-4,7-megastigmadien-3-one (M-2), (3S,5R,8R)-3,5-dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Connections with many previous and current data of kojic acid and arbutin depigmenting assay in vitro (i.e., melanocytes) and in vivo (i.e., mice) help to support current investigation and better understanding using zebrafish embryo [13,57]. For instance, compound bis(4-hydroxybenzyl)sulfide reduces pigmentation level to about 41% (a percentage relative to untreated control), lower than arbutin and kojic acid, which indicates that bis (4-hydroxybenzyl)sulfide had a better depigmenting activity as compared to that of arbutin and kojic acid [13]. In addition, it was revealed that the bis(4-hydroxybenzyl)sulfide reduces melanogenesis in zebrafish comparably as effective as indicated by reduced melanin content, TYR, TRP-1, MITF in melanocytes in vitro [6,13].…”
Section: Application Of Zebrafish Modelmentioning
confidence: 75%
See 4 more Smart Citations
“…Connections with many previous and current data of kojic acid and arbutin depigmenting assay in vitro (i.e., melanocytes) and in vivo (i.e., mice) help to support current investigation and better understanding using zebrafish embryo [13,57]. For instance, compound bis(4-hydroxybenzyl)sulfide reduces pigmentation level to about 41% (a percentage relative to untreated control), lower than arbutin and kojic acid, which indicates that bis (4-hydroxybenzyl)sulfide had a better depigmenting activity as compared to that of arbutin and kojic acid [13]. In addition, it was revealed that the bis(4-hydroxybenzyl)sulfide reduces melanogenesis in zebrafish comparably as effective as indicated by reduced melanin content, TYR, TRP-1, MITF in melanocytes in vitro [6,13].…”
Section: Application Of Zebrafish Modelmentioning
confidence: 75%
“…The application of zebrafish depigmenting assay was supported by the effect of well-known bioactive agents such as kojic acid and arbutin on embryo depigmenting activity [40,57,58]. Connections with many previous and current data of kojic acid and arbutin depigmenting assay in vitro (i.e., melanocytes) and in vivo (i.e., mice) help to support current investigation and better understanding using zebrafish embryo [13,57]. For instance, compound bis(4-hydroxybenzyl)sulfide reduces pigmentation level to about 41% (a percentage relative to untreated control), lower than arbutin and kojic acid, which indicates that bis (4-hydroxybenzyl)sulfide had a better depigmenting activity as compared to that of arbutin and kojic acid [13].…”
Section: Application Of Zebrafish Modelmentioning
confidence: 94%
See 3 more Smart Citations